2011
DOI: 10.1007/s10096-011-1180-7
|View full text |Cite
|
Sign up to set email alerts
|

Burden of rotavirus infections in Liguria, northern Italy: hospitalisations and potential savings by vaccination

Abstract: Purpose We evaluated the rates of gastroenteritis admissions to the emergency department and of rotavirusrelated hospitalisations in children ≤5 years in 2006 at an Italian paediatric hospital; we calculated the number of rotavirus cases avoidable through the universal vaccination of children.Methods Epidemiological data were extracted from the Data Elaboration Centre. To calculate the hospitalisation rate due to rotavirus, the virus was sought in the faeces of children hospitalised for acute gastroenteritis b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Rotavirus (RV) infection is the primary cause of viral acute gastroenteritis (GE) in infants and children <5 years old. 1,2 It is estimated that by the age of 5 years, nearly every child will have had at least one episode of rotavirus gastroenteritis (RVGE). 3 Although maintaining good hygiene like handwashing, sanitation along with exclusive breastfeeding for 6 months, vitamin A supplementation and safe drinking water are essential to prevent the spread of infections, RV vaccination has proven to be the most effective approach to protect children against RVGE disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rotavirus (RV) infection is the primary cause of viral acute gastroenteritis (GE) in infants and children <5 years old. 1,2 It is estimated that by the age of 5 years, nearly every child will have had at least one episode of rotavirus gastroenteritis (RVGE). 3 Although maintaining good hygiene like handwashing, sanitation along with exclusive breastfeeding for 6 months, vitamin A supplementation and safe drinking water are essential to prevent the spread of infections, RV vaccination has proven to be the most effective approach to protect children against RVGE disease.…”
Section: Introductionmentioning
confidence: 99%
“…Fundamentally, the clinical severity and diverse outcomes of RVGE in infants are known to exert substantial emotional and social impact (direct and indirect) on their families. [1][2][3] RVGE affects young children at a crucial time of physical and emotional development with consequences on cognitive development and it has also been suggested that diarrhea in childhood is linked to adult chronic diseases such as cardiovascular diseases, diabetes, obesity, and hypertension. [4][5][6] As RVGE is characterized by a sudden onset it can disrupt daily routines of the family which can require unexpected changes, and can consequently affect the physical, emotional and social well-being of the child and its family.…”
Section: Introductionmentioning
confidence: 99%
“…44 estimates show that a 90% rV vaccination coverage would significantly decrease disease burden in european regions. 45,46 it has also been suggested that an rV vaccination coverage rate of about 90% might induce herd immunity, which may play a vital role in reducing the number of nosocomially acquired rV diseases.. 47,48 a limitation of this study is that the survey began after the new rV vaccine was approved. as some federal states have already implemented the rV vaccine in their local vaccine recommendations, this may have caused a reduction in the number of vsrVd as the rV vaccine reduces the rate of rV hospitalizations.…”
Section: Discussionmentioning
confidence: 96%
“…This study only assessed rotavirus AGE cases, but not cases of AGE of different etiology or AGE due to unspecified viral infections. As Gil-Prieto et al 17 pointed out, rotavirus AGE is not a reportable disease in Spain and many pediatricians do not ask for specific tests because the treatment does not significantly change. These authors found a 24% of rotavirus-coded hospitalizations in children <5 years, but also a 15% of undetermined etiology diarrhea, and they suggested that part of diarrhea cases coded as non-rotavirus AGE could be non-diagnosed rotavirus AGE.…”
Section: Discussionmentioning
confidence: 99%
“…8 Reductions in hospitalizations due to rotavirus AGE have been reported in many countries in Europe [9][10][11][12][13][14][15][16] and mathematical models have calculated a huge impact on the burden of rotavirus disease. 17 In the United States, where the rotavirus vaccine is recommended for routine immunization of infants, the rate of hospitalizations due to rotavirus AGE is also reduced. 18,19 Currently licensed rotavirus vaccines include a pentavalent rotavirus vaccine (RotaTeq Ò , Sanofi Pasteur MSD) and a monovalent rotavirus vaccine (Rotarix Ò , GlaxoSmithKline).…”
Section: Introductionmentioning
confidence: 99%